Testing aptitude for simultaneous interpreting: the predictive validity of recall and lexical-syntactic flexibility test - Lu, Xinchao; Xu, Xiuling (The interpreter and translator trainer, 2023)
Developing effective aptitude test batteries for conference interpreting is highly relevant for China given its large and fast-growing interpreting trainee population. This paper reports on the aptitude tests implemented to 23 first-year students at a CIUTI member and UN MOU university in China. We compared the validity of recall, a test commonly used in interpreting aptitude testing, with that of the lexical-syntactic flexibility test (LSFT) newly developed at the university, in predicting the students' subsequent performance on simultaneous interpreting (SI) exams. The quantitative analyses of recall, LSFT and SI data using correlation and multiple regression analysis were backed up by qualitative analyses of students' output and interview data. The results suggest that recall, believed or found to be a predictor of interpreting aptitude by some studies, is not predictive of the Chinese (A)-English (B) SI performance, while the LSFT significantly predicts the performance of bidirectional Chinese (A)-English (B) SI and could be a potential SI-specific aptitude predictor and a new testing option to add to the existing pool of text-based tests. The study is expected to inform the discussion and practice of aptitude testing for conference interpreting in China and to shed light on aptitude testing worldwide.